中国反贫困问题及宏观政策探讨 = An analysis of China's anti-poverty policies - 李石 Li, Shi (2008)
Based on various existing definitions of poverty, this paper gives an account on the measurements of poverty and the distribution of China's poor regions. It also provides a detailed analysis on the efficacy and achievements of China's anti-poverty policies. Furthermore, it explores the issues and options regarding poverty alleviation that the Chinese government has to face in the 21st century. Finally, it proposes a series of anti-poverty policies that should be implemented in the immediate future.